Work Engagement as a Mediator of Organizational Citizenship Behavior towards Patient Safety Culture at Hospital X Jakarta - Novadiana, Novadiana; Arrozi, MF; Indrawati, Ratna (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to obtain empirical evidence of the influence of psychological capital and organizational citizenship behavior on patient safety culture with work engagement as an intervening variable. This research uses an explanatory causality method with. The population of all health workers at Hospital X Jakarta is 108 people. The sampling technique uses the Non-Probability Sampling method, by distributing questionnaires to all samples, which are then analyzed using Structural Equation Modeling (SEM). The test results show that psychological capital, organizational citizenship behavior, and work engagement simultaneously influence patient safety culture at RS X Jakarta. Psychological capital and work engagement have been proven to influence patient safety culture. However, organizational citizenship behavior has no effect on patient safety culture at Hospital X Jakarta. Psychological capital and organizational citizenship behavior have a significant effect on work engagement at RS X Jakarta. Work engagement is proven to be a mediator in the influence of organizational citizenship behavior on patient safety culture. The novelty of this research is a study contribution to fill the gap that occurs from work engagement as a mediation from Organizational Citizenship Behavior to Patient Safety Culture